Cities of tomorrow : an intellectual history of urban planning and design since 1880 - Hall, Peter, 1932-2014 (Wiley-Blackwell, 2014)
"Peter Hall's seminal Cities of Tomorrow remains an unrivalled account of the history of planning in theory and practice, as well as of the social and economic problems and opportunities that gave rise to it. Now comprehensively revised, the fourth edition offers a perceptive, critical, and global history of urban planning and design throughout the twentieth-century and beyond. A revised and updated edition of this classic text from one of the most notable figures in the field of urban planning and design Offers an incisive, insightful, and unrivalled critical history of planning in theory and practice, as well as of the underlying socio-economic challenges and opportunities Comprehensively revised to take account of abundant new research published over the last decade Reviews the development of the modern planning movement over the entire span of the twentieth-century and beyond Draws on global examples throughout, and weaves the author's own fascinating experiences into the text to illustrate this authoritative story of urban growth "--